MAGNETO-HYDRODYNAMIC EFFECTS ON DIESEL/CNG BUBBLY FLOW IN A HORIZONTAL PIPE - ABDUL WAHHAB, HASANAIN ADNAN (2018)
The magneto-hydrodynamics of diesel in a two-phase laminar flow in horizontal pipe was studied. The diesel was enhanced with iron oxide (Fe3O4) nanoparticles. Then, drag reduction by magneto-hydrodynamics in the liquid/gas fuel mixtures has been used, due to the increase electrical properties of liquid fuel after addition nanoparticles, thereby creating a higher magnetic field effects in the line. Drag reduction caused by magneto-hydrodynamic effects on the diesel/gas fuel mixture was investigated experimentally as well as theoretically.